2014
DOI: 10.3233/cbm-140414
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of S100A4 expression enhances invasive and metastatic potentials of COLO16 cutaneous squamous cancer cells

Abstract: S100A4 confers invasive and metastatic potentials on human c-SCCs. The low incidence of metastasis of c-SCCs, especially the well differentiated ones, might be due to the infrequent S100A4 expression. S100A4 can be regarded as a negative prognostic biomarker or a metastasis-risk factor of human c-SCCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Next, our study demonstrated that silencing of S100A4 restrained the viability, migration, and invasion of rCSCs in virto. 8 , 37 , 38 The promotion in cancer cell migration and invasion mediated by overexpression of S100A4 has been suggested in several human cancers, such as cutaneous squamous cancer, 39 hepatocellular carcinoma, 40 and squamous cell laryngeal cancer. 41 Our study suggested that S100A4 also modulated those capacities of rCSCs, through which S100A4 silencing was conducive to wound repair.…”
Section: Discussionmentioning
confidence: 99%
“…Next, our study demonstrated that silencing of S100A4 restrained the viability, migration, and invasion of rCSCs in virto. 8 , 37 , 38 The promotion in cancer cell migration and invasion mediated by overexpression of S100A4 has been suggested in several human cancers, such as cutaneous squamous cancer, 39 hepatocellular carcinoma, 40 and squamous cell laryngeal cancer. 41 Our study suggested that S100A4 also modulated those capacities of rCSCs, through which S100A4 silencing was conducive to wound repair.…”
Section: Discussionmentioning
confidence: 99%
“…S100A4 is regarded as an important regulator of metastasis and EMT . Overexpression of S100A4 promotes metastasis in several experimental animal models, in contrast, down‐regulation of S100A4 expression reduces the metastatic capacity of cancer cells . In CRC, S100A4 is overexpressed and its expression is correlated with patient outcome .…”
Section: Discussionmentioning
confidence: 99%
“…[51][52][53] Overexpression of S100A4 promotes metastasis in several experimental animal models, in contrast, down-regulation of S100A4 expression reduces the metastatic capacity of cancer cells. 24,51,[54][55][56][57][58] In CRC, S100A4 is overexpressed and its expression is correlated with patient outcome. 59,60 Consistent with that, our results showed that the expression of S100A4 was higher in human CRC tissues compared with their normal counterpart tissues, and higher expression of S100A4 was significantly correlated with lymph node metastasis and poor survival.…”
Section: Trx-1 Knockdown Inhibits Crc Cell Migration and Invasion Abimentioning
confidence: 99%
“…S100A4 is also named as FSP (fibroblast‐specific protein) because of its preferable expression in fibroblasts (Österreicher et al, ) or Mts1 (metastasin) as its close correlation with cancer metastasis (Rasanen et al, ). Consequently, S100A4 silencing inhibits invasive ability of human colorectal and pancreatic cancer cells (Dahlmann et al, ; Li et al, ), and restoration of its expression enhances metastatic potential of squamous cell carcinoma of the skin (Yu et al, ).…”
Section: Introductionmentioning
confidence: 99%